A traumatism is in a womanish handball - Strikalenko, E. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Character of the most widespread traumas is considered in the Ukrainian womanish handball, facilities of rehabilitation after the different kinds of traumas are generalized and the percent of returning of sportswomen is returned after the different types of traumas. 122 handballers took part in research, which come forward in the commands of Ukrainian Super league. During research a questionnaire and questioning of players, doctors and trainers of leading handball clubs was used. It is set that the most of traumas is on the damage of overhead and lower extremities (38 % but 26 % accordingly). Distributing of cases of traumatism following between the players of different playing line of business: for linear players 26 %, goalkeepers (24 %), extreme players (20 %), who play, and welterweight 14 % but 16 % accordingly. It is set during research, that 63,2 % sportswomen are used conservative method of treatment, and 36,8 % handballers are applied operative method of treatment. It is experimentally set that most percent of failure to return of handballers to active contention activity after tears and breaks of copulas (every third sportswoman), after the delete of meniscuses - every fourth, every fifth handballer did not return after the concussions of the brain. A traumatism in sport remains one of main problems of his existence.